An exploratory study on the prospect of Virtual Reality's key multi-sensory elements in traditional foot reflexology - Chimeremeze, O.H. (Institute of Electrical and Electronics Engineers Inc., 2014)
This paper explores the potential application of Virtual Reality (VR) in the traditional foot reflexology (TFR) domain. The simulation of foot reflexology has since been a significant area of interest that has led to the development of manual artifacts and electronic stimulators/vibrators. However, there has been very little attention given towards identifying the existence of the three VR multi-sensory elements and the virtualization of the therapy. The study presented in this paper examines the multi-sensory interactive prospects of VR's key multi-sensory elements (visual, aural and hap tics) interactions in TFR. The interactions between the practitioner and patients in two traditional foot reflexology sessions were observed, and these participants were also interviewed. The study findings indicate the existence of the three VR multi-sensory elements in TFR and identified their interactive nature. Implications for future research are also discussed. Â© 2013 IEEE.